Specificity of prohormone convertase endoproteolysis of progastrin in AtT-20 cells. - Dickinson, C J (1995)
Biologically active peptide hormones are synthesized from larger precursor proteins by a variety of posttranslational processing reactions. Endoproteolytic cleavage at the Lys74-Lys75 dibasic processing site of progastrin is the major determinant for the relative distribution of gastrin heptadecapeptide and tetratriacontapeptide in tissues. Thus, we explored the ability of two prohormone convertases, PC1/PC3 and PC2, to cleave this important site within progastrin. We expressed wild-type human gastrin cDNA and mutant cDNAs in which the Lys74Lys75 site was changed to Lys74Arg75, Arg74Arg75, and Arg74Lys75 residues in AtT-20 cells. Because AtT-20 cells express Pc1/PC3 but not PC2, we also coexpressed a cDNA encoding PC2 in both wild-type and mutant gastrin-producing AtT-20 cells. Wild-type Lys74Lys75 and mutant Arg74Arg75 progastrin processing sites were efficiently cleaved in AtT-20 cells only after coexpression of PC2. Mutant Lys74Arg75 progastrin was readily processed in cells in the presence or absence of PC2 coexpression, but, in contrast, mutant Arg74Lys75 progastrin was inefficiently cleaved regardless of PC2 coexpression. Northern analysis revealed the presence of PC2 but not PC1/ PC3 in canine antral gastrin-producing G cells. These data suggest that PC2 but not PC1/PC3 is responsible for the cleavage of the Lys74Lys75 site in wild-type progastrin.